The Fight for the Right to Food - Ziegler, J. author. aut Link
XX, 440 p.
Keywords: This book documents and analyzes the experiences of the UN's first Special Rapporteur on the Right to Food. It highlights the conceptual advances in the legal understanding of the right to food in international human rights law, as well as analyzes key practical challenges through experiences in 11 countries across Africa, Asia and Latin America.